Consumption of signs in preloved cultural practices among Generation Z in market places - Rahmah, Hilda; Fanani, Fajrian Noor; Pamung, Yoma Bagus (Universitas Bunda Mulia, 2023)
This research aims to determine the form of sign consumption in preloved cultural practices among Generation Z at the Shopee marketplace. This research uses the ethnographic method to highlight community or community activities in a virtual space. In this case, Generation Z, aged 19-26, is active in the preloved culture at the Shopee marketplace. Massively increasing preloved practices among Generation Z marketplace users have brought a new discourse. Preloved is a term used to define and classify privately owned clothing that is resold. Usually, preloved goods offer quality from well-known brands, thereby attracting consumer appeal, especially for Generation Z. Generation Z consumers have a decision-making style that is sensitive to brands, prices, perfectionists, emphasizes quality, hedonic, impulsive, and loyal, so that in practice they often target branded goods, even though they are not new or can be called preloved. Symbolically, preloved fashion items, often the target of Generation Z, become an alternative to fulfill their desire to show their self-image through the brand they wear. In line with Baudrillard's perspective, this practice is not only done to meet needs but is simultaneously used to consume signs and symbols that emphasize the brand attached to the goods. Furthermore, the consumption of signs by the Z gene shows the form of social capital (building networking), economic capital (financial security), culture capital (interpersonal skills), and symbolic capital (recognition), where this capital becomes capital accumulation for gen Z in its efforts to adapt and social mobility in the digital age.